The Sword of the Word: The Use of Hyperbole in The Political Cartoons of Indonesians - Nugraha, Danang Satria (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. This study utilizes Critical Discourse Analysis (CDA) to scrutinize the rampant use of hyperbole in Indonesian political cartoons. The objective is to assess how exaggerated language and visual representations are utilized to communicate political messages within a socio-cultural context. Through analyzing various cartoons from Kompas.id in Indonesia (period of publication: January 2019 up to July 2023), as the main data, this study exposes how hyperbolic elements are practical tools in shaping public opinion and impacting political discourse. The findings of this study offer vital insights into the influence of hyperbole in the cartoonistic medium. The strategic use of exaggerated language and visuals in cartoons influences the reception of political messages and shapes public discourse. It comprehensively comprehends how these visual narratives contribute to the dynamics of Indonesian politics. This study contributes to a broader discourse on political communication and media studies, providing an understanding of the complex interplay between language, imagery, and power within Indonesia’s sociopolitical landscape. Keywords: Hyperbole, Political cartoons, Indonesians, Discourse, Linguistic